Penerapan Modifikasi Perilaku Teknik Fading untuk Mengurangi Perilaku Agresif pada Anak Usia Dini - Ilmenia Zulianty; Assri Fitrida Putri; Hanisa Azura; Maia Welia Dinda; Rafly Rafly; Syerli Akhla Rosa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Deviant and negative behavior that we often encounter in children aged 2, 3 to 5 years is also called aggressive behavior. This attitude tends to cause harm to others if this behavior has shown an attitude of hurting or physically attacking. Internal and external factors can be the cause of a child behaving aggressively. Therefore, aggressive behavior can be reduced using certain techniques or methods, one of which is the fading technique. The purpose of this study was to reduce aggressive behavior in early childhood using the fading technique. The research design used in this study was Single Subject Design (SSD) or research with a single subject. The data collection technique used in this study used the observation technique with behavioral tally recording. In the study, 10 intervention sessions were carried out for 7 days with the results of a low aggressiveness categorization with a total score of 54 in the range of 52.5 <X ≤ 67.5. So it can be concluded that there is effectiveness in implementing the fading technique in an effort to minimize aggressive behavior.